2023
DOI: 10.3389/fnut.2022.1103838
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freezing-thawing on the quality changes of large yellow croaker treated by low-salt soaking during frozen storage

Abstract: IntroductionThe production of the large yellow croaker has seasonal and regional characteristics, which is typically preserved on ice, possibly leading to its deterioration in a short time. Therefore, in this study, we focused on the effect of temperature fluctuation on the quality changes of the large yellow croaker during frozen storage.MethodsIn this experiment, the large yellow croaker was soaked in a low-salt solution, and physical and chemical properties, water-holding capacity, color, and protein charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Nosocomial infections, such as Stenotrophomonas maltophilia and Acinetobacter baumannii , are resistant to most antibiotics. Interestingly, TFs have an obvious bacteriostatic effect on these pathogens, and the effect is more significant when used with epicatechin (EC) (Mao, 2021).…”
Section: Health Benefits Of Tpgsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nosocomial infections, such as Stenotrophomonas maltophilia and Acinetobacter baumannii , are resistant to most antibiotics. Interestingly, TFs have an obvious bacteriostatic effect on these pathogens, and the effect is more significant when used with epicatechin (EC) (Mao, 2021).…”
Section: Health Benefits Of Tpgsmentioning
confidence: 99%
“…Sun et al (2017)) showed that TFs can be used as a natural antioxidant to control the melanosis of shrimp. Mao (2021), (Cui et al, 2020) proved that TFs slowed the decomposition of protein and lipid in large yellow croaker, which significantly delayed the quality changes in fish during frozen storage. Therefore, TPGs, in combination with other preservatives or modern biotechnology, can play an important role in food preservation.…”
Section: Limitations and Potential Applications Of Tpgsmentioning
confidence: 99%
See 1 more Smart Citation